Evaluation of the Effects of Oronasal Versus Oral Disinfections with Chlorhexidine on Clinical Criteria of Ventilator-associated Pneumonia - Mahdi Alimi; Zahra Sadat Manzari; Seyed reza Mazlom; Ahmad Bagheri Moghadam; Hossein Rouhani (Mashhad University of Medical Sciences, 2016)
Background: Ventilator-associated pneumonia (VAP) is the most prevalent and lethal form of nosocomial infections in the ICU and oral disinfection is a nursing measure to prevent this condition. Aim: this study aimed to evaluate the effect of oronasal versus oral disinfections with chlorhexidine on the clinical criteria for diagnosis of VAP. Method: This randomized clinical trial was conducted on 70 intubated ICU patients under mechanical ventilation at Shahid Kamyab Hospital of Mashhad, Iran in 2016. Samples were divided into two groups of intervention (mouthwash and disinfection of nostrils with 0.2% chlorhexidine every eight hours) and control (mouthwash). Clinical criteria for VAP, including pulmonary infiltration, rectal temperature, white blood cell (WBC) count and endotracheal discharge were recorded and compared between the two groups from days 1-6. Data analysis was performed in SPSS version 11.5 using Chi-square test. Results: In this study, mean age of intervention and control groups was 44.3±19.9 and 45.9±18.2 years, respectively. The results of Chi-square test indicated no significant difference between the groups regarding rectal temperature (P=0.22), WBC count (P=0.33), purulent endotracheal discharge (P= 0.47), pulmonary infiltration (P=0.21) and incidence of VAP (P=0.21). Implications for Practice: According to the results of this study, no statistically significant difference was observed between the two groups regarding clinical criteria and the incidence of VAP despite clinical differences. Therefore, it is recommended that further studies be conducted in this area.